Between the Stage and the Page: Printed Marginalia in Gascoigne’s Supposes - Ragni, Cristiano (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This article analyzes printed marginalia in the 1573 and 1575 editions of Gascoigne’s Supposes, highlighting their liminal dimension, typical of early modern English playbooks, between printed and performative textuality. The printed marginalia in the 1573 edition not only are annotations that speak from the margins of the possible performance of the text but can also be read as a sign of cross-fertilization between coexisting types of drama. The marginalia in the 1575 edition clearly aim at readers of the playbook rather than at spectators of future performances. In this sense, they are unlikely Gascoigne’s originals, but the result of interventions by those involved in the volume’s printing. The article explores how the printed marginalia in these two editions of Gascoigne’s Supposes suggest intriguing relations between the play’s textual and performative dimensions.